Fortalecimiento de las habilidades científicas: investigación, representación y comunicación a través de una estrategia multisensorial para estudiantes de segundo de primaria en la CED Cedid Ciudad Bolívar. - Acosta Leal, Yeimy (Universidad Antonio Nariño, 2022)
The development of scientific skills in students in the first grades of primary basic education has great relevance since it is the way to associate the reality of their context with scientific knowledge through the appropriation of meaningful strategies. This research was generated from a qualitative approach and a descriptive scope; seeking to strengthen scientific research, representation and communication skills based on a multisensory strategy in second grade students from an official institution of Colombia. The methodological process was in three phases: the entry test, which informed results that served as a basis for the planning of the multi-sensory strategy focused on topics of Natural Sciences. The multi-sensory strategy that allowed to involve the children and led them an exploration from the senses, to address scientific skills; and the exit test that allowed to generate a reflection on the importance of working with scientific skills.